[quote author=dsantamassino link=board=14;threadid=7355;start=0#msg67853 date=1057954992]
Hey Lovechild and everyone. I can't even do simple algebra. When the time comes what should i do for nagitive exponents?? And square roots raise to a power??
One step at the time, let's get the algebra down first then we can work on the more advanced stuff later..
I would really look around for a tutor if I was you, a few hours in person training can do wonders, especially for brushing up on basic stuff like algebra and other common concepts.
I'm happy to help but doing this over the internet is really not that easy.
[quote author=dsantamassino link=board=14;threadid=7355;start=0#msg67857 date=1057955748]
If you ask me i'm kind of cheating by writing down what you told me just now. I don't have a clue. Can we try a different and easier method with less confused?? Please reply back.
I'm not much for using another method - I would rather explain to you why this is good, it's good because it works every time and it's absolutely straightforward once you get a hang of it, don't worry it took me a while also.
[quote author=dsantamassino link=board=14;threadid=7355;start=0#msg67861 date=1057956035]
yeah thats it. What i don't understand is everything. I told you what i did and i guess i did it wrong.
Okay, here are the basics.
You can extend a division by 1 without it changing the value of the division.
Here we use that to turn two divisions into one.
1 can be written as fx.
--- or ---
Now multiplication of a fraction with another faction is simple
just multiple directly like this:
2 4 2 * 4 8
--- * --- = ------ = ---
3 2 3 * 2 6
Now we use this to extend all divisions in the problem by one - since that doesn't alter the value of the total equation it's perfectly legal.
Now we want to get one division so we extend by one using
--- + ---
---- = 1
Freely extend the other division but this - following the prior rule:
1 1 * 2x
--- + -------
2x 3x * 2x
Now we do the same to the other division, but here we of course use the other division to pick our constant.
1 * 3x 1* 2x
-------- + ---------
2x * 3x 3x * 2x
The point here is getting the same in this section
y <=== HERE
because then they have a common divisor and thus we are allowed to do this
1 * 3x + 1* 2x
2x * 3x
This has the same value still.
Now we can clean up a bit
3x + 2x
And now we have a single division with which to continue calculations.